QUALITY AND SAFETY OF PUBLIC CATERING SERVICES IN UZBEKISTAN - Dehkonov Burhan Rustamovich (European Journal of Life Safety and Stability (2660-9630), 2021)
The article discusses a scientific and theoretical explanation of safety issues in the organization of public catering, as well as in order to further improve the system of catering for personnel of units and security, the provision of food services in the Republic of Uzbekistan. The topic is analyzed on the basis of regulatory legal acts and practical recommendations for public catering enterprises in Uzbekistan.